Professional training of future specialists with the use of information technologies - V S Kornilov; K M Berkimbayev; D Zh Ernazarova (RUDN Journal of Informatization in Education, 2013)
This paper deals with implementation of information technologies within different levels of professional training of the future specialists at A. Yassawi International Kazakh-Turkish University. Information technologies enable the future specialists to engage in online exchanges and it gives great good opportunity in learning the subject efficiently; thereby expanding their study and learning community during the classroom activity. The results obtained by the use of the information technologies show improvements in professional training of the future specialists in teaching foreign language. The use of information technology in teaching is increasing, which should lead to a significant improvement of the training quality of future specialists. Improvements also are observed in the experimental groups of higher levels, which indicates the efficiency of the use of information technologies in the professional training of future specialists.